Development of an E-Module on Animal Locomotor Organs for Fifth-Grade Students Based on Canva and Liveworksheet - Fauziah, Popon Siti; Hadi, Muhammad Sofian (Indonesian Journal of Primary Education, 2025)
The 21st century demands that educators transform conventional teaching methods into digital formats. Teaching modules provided by teachers in printed form often fail to effectively facilitate students' understanding of the material, particularly on the topic of animal locomotion organs. This study aims to develop an innovative and feasible E-Module based on Canva and Liveworksheet, tailored for fifth-grade elementary school students. The research employs the ADDIE model, comprising five stages: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. Data collection techniques included observation, interviews, and questionnaires with a rating scale. The research subjects were fifth-grade teachers and students. Media validation was conducted through assessments by subject matter experts, design experts, and learning communication media experts. Results showed that the subject matter validation achieved a score of 92% (very feasible category), design validation achieved a score of 96% (very feasible category), and media communication validation achieved 95% (very feasible category). The E-Module based on Canva and Liveworksheet is concluded to be highly suitable for teaching the topic of animal locomotion in fifth-grade elementary school.